In pursuit of unconventional love exploring relationships resilience among Filipino young adults in consensually non-monogamous (CNM) relationships - Ripalda, Pierce Coleine; Pestilos, Cristy C. (2023)
This research paper explores the challenges, coping strategies, and resilience of individuals in consensually non-monogamous (CNM) relationships. Drawing on the framework of the minority stress model, the study examines the unique stressors faced by CNM individuals and the ways in which they navigate and overcome these challenges. The research utilizes a qualitative approach, involving in-depth interviews with a diverse sample of CNM individuals recruited from a specific Facebook group dedicated to CNM relationships. The findings reveal that emotional distress, particularly related to jealousy and conflicting pre-existing beliefs, emerges as a key challenge in CNM relationships. Coping strategies such as effective communication and introspection play a vital role in managing these challenges and fostering resilience. Additionally, the study identifies four core components of CNM resilience: healthy communication skills, embracing the uncomfortable process of learning and taking risks, personal resilience, and positive connections within supportive networks. The research contributes to a comprehensive understanding of CNM resilience and provides insights for future studies. Limitations and suggestions for future research are discussed, including the need for a more diverse sample and consideration of cultural factors. Comparative research between CNM and monogamous relationships is also recommended to inform interventions promoting healthy relationship functioning across diverse relationship styles.
Undergraduate thesis (B.A. Psychology) --University of the Philippines, Tacloban.